A systematic literature review of the Pay-What-You-Want pricing under PRISMA protocol - Oktay Güzel; Emili Vizuete-Luciano; José María Merigó-Lindahl (European Research on Management and Business Economics)
This study aims to systematically examine the Pay-What-You-Want (PWYW) pricing model, which has become increasingly popular among innovative strategies. The PWYW model offers an unconventional approach by giving consumers the power to determine the price they want for the goods or services provided. However, the scattered nature of existing research makes it challenging to understand this model's dynamics fully. Using the PRISMA protocol, this systematic review of 106 articles reveals the key actors, theoretical frameworks used, and methodological trends in the known aspects of the field. In addition, the findings highlight the potential advantages of PWYW pricing (e.g., transparency and customer preference) while revealing critical gaps in the current knowledge. This study is important because it provides a holistic perspective on the PWYW pricing model literature, which seems to be a significant deficiency. The study emphasizes the need to investigate understudied areas, such as the sustainability of PWYW and the interaction of factors affecting payment behaviors. This review guides how PWYW practices can be managed effectively in a changing business world, helping businesses navigate their future implementation.